Masnavi Taqdis and Masnavi Manavi - hasan haidari (Matn/Pizhūhī-i Adabī, 2014)
Rumi’s Masnavi has been the center of attention of other poets as one of the most famous mystical works. That is why there are many imitations of the book. One of the Masnavis which is similar to Rumi’s Masnavi in form and content is Masnavi Taqdis and is written by Molla Ahmad Naraqi. This paper compares these two Masnavis with a critical approach. As for formal factors, the comparison between these two works show that one of the important factors of association in Masnavi is the one based on similarity. This type of association too has branches in Rumi’s Masnavi such as association through the theme or based on the attributes of the characters, dialogues, synopsis, etc. The present paper attempts to show these similar cases in Masnavi Taqdis. The rhythm and form of the two Masnavis are among other similarities that can be discussed. In addition, both works start without any preparation and the first verse begins with the word “hear”. The ending in both Masnavis are also similar because both of them are unfinished. The this study shows that Masnavi Manavi is superior to Masnavi Taqdis in the common stories and the method of developing them. In terms of content, besides the fact that different mystical issues are mentioned in these two Masnavis, some stories are common in these two works. Molla Naraqi has adopted large number of verses from Masnavi Manavi.